The Effect of Al-Qur'an Murottal Therapy on Breastfeeding Anxiety in Primipara Postpartum Mothers - Amabel, Meilia; Rahayu, Budi (Universitas Muhammadiyah Yogyakarta, 2023)
The psychological condition of primiparous postpartum mothers will experience anxiety in breastfeeding caused by the calmness or comfort of the mother's soul. Spiritual activities such as listening to Al-Qur'an murottal may affect this psychological condition. This study aims to determine the effect of Al-Qur’an murottal therapy on breastfeeding anxiety in primiparous postpartum mothers. This study is a pre-experimental quantitative study with a one-group pretest-posttest design. There were 33 respondents of primiparous postpartum mothers’ day 3-10 involved in this study came from the Independent Practice Midwife in Central Java. The inclusion criteria included Moslem, physically and mentally healthy, and communicative. The exclusion criteria are preeclampsia, eclampsia, and bleeding sufferer. The dependent variable was anxiety, assessed by the Hamilton Anxiety Rating Scale (HARS). The average anxiety score before therapy was 31.79 (severe) and 13.58 (mild) after therapy. Different tests using the Wilcoxon Test showed significant differences in anxiety scores before and after therapy (p 0.000). It can be concluded that Al-Qur'an murottal therapy had an effect on breastfeeding anxiety in primiparous postpartum mothers. Thus, the Al-Qur’an murottal can be used to reduce anxiety during breastfeeding, especially in primiparous postpartum mothers.